Obstructive sleep apnea associated with Diabetes mellitus Type 2: a proteomic study - Vaz, Fátima (2019)
Background: We previously showed that Obstructive sleep apnea (OSA), a common public health concern causing deleterious cardiometabolic dysfunction, induced proteomic alterations in red blood cells (RBC) such as changes in the redox-oligomeric state of peroxiredoxin 2 (PRDX2)1-2. Herein, we aimed to investigate whether OSA patients with Type 2 Diabetes Mellitus before and after positive airway pressure (PAP) treatment present similar changes in the RBC antioxidant protein PRDX2 to better understand the molecular basic mechanisms associated with OSA and OSA outcomes. Methods: RBC samples from control snorers (n=22 being 3 diabetics) and OSA patients before and after six month of PAP-treatment (n=29 being 8 diabetics) were analysed by non-reducing western blot using antibody against PRDX2 or PRDXSO2/3 to measure the total and overoxidized levels of monomeric/dimeric/multimeric forms of PRDX2. Results: We confirmed previously data by showing that in OSA RBC the overoxidation on the monomeric forms of PRDX2 was higher compared to controls. After PAP treatment, this overoxidation decreased followed by an increase of multimeric-overoxidized forms of PRDX2 described to be associated with chaperone protective function. In contrast, the level of PRDX2 monomers in RBC diabetic OSA, although higher abundant its overoxidation level was much lower than those observed in OSA without comorbidity and did not significant change after treatment. Moreover, the level of PAP-induced PRDX2-overoxidized-multimers was also lower in these diabetic OSA patients. The level of overoxidized monomeric/dimeric forms of PRDX2 correlated negatively with levels of insulin / triglycerides and HbA1C, respectively. After PAP, the level of (overoxidized) PRDX2SO2/3 multimers correlated positively with adrenaline levels. Conclusions: The redox/oligomeric state of RBC PRDX2 that is regulated by overoxidation of the active cysteines was differentially modulated in diabetic OSA patients compared to OSA without this comorbidity. PAP-induced overoxidized oligo forms of PRDX2 that is associated with chaperone protective function showed decreased in OSA patients with diabetes. The clinical impact of these findings needs further investigation and validation.